Quem se torna bolsista de iniciação científica na UFMG?: uma análise de fatores que influenciam no acesso à bolsa - Mariana Gadoni Canaan (2012)
This dissertation aims to analyze the distribution of scientific initiation scholarships at UFMG. The work was guided by some basic questions: who are the scholarship holders? How and why do they become scholarship holders? In order to answer these questions, different research methods and techniques have been used: a) the execution of a cohort study; b) the treatment of secondary statistical data about entrants into the Biological Sciences, Electrical Engineering, and History undergraduate programs in the years 2007, 2008, and 2009; c) semi-structured interviews with twelve scientific initiation scholarship holders attending the three programs analyzed. The results have made evident that the average profile of the scientific initiation scholarship holder does not differ significantly from the average profile of the students in the programs analyzed. They are, in their majority, young, white, single, members of the middle class of Belo Horizonte and surrounding areas, whose parents have higher levels of education, and who have a successful educational background. Albeit the similar profiles, some socioeconomic factors increase the chances of a student becoming a scientific initiation scholarship holder during undergraduate studies. These factors vary among the programs analyzed. The History program was the only one in which the study's initial hypothesis has been confirmed, namely, the possession of cultural capital proved to be advantageous in terms of access to the scholarship, as well as economic capital. As opposed to the expectations, in the case of the Biological Sciences program, a larger cultural capital means less chance of access to the scholarship. In the case of the Electrical Engineering program, only the educational capital seems to bring some advantage to the scholarship attainment. The motivations that stimulate the student toward scientific initiation don't differ significantly according to the program and the social background. Search for advancement in topics of interest, research techniques and methods learning, concern with insertion in the university's operational logic, and academic record improvement aiming graduate programs stand out. Nevertheless, the social background seems to affect the students' mobility: students of socioeconomic segments C and D are more prone to developing strategies for scholarship attainment, such as approaching professors, doing volunteer work, searching for scholarships in other departments of the university, searching for scholarships in research fields where more resources are available, etc.